2017
DOI: 10.1038/s41598-017-15435-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Meaningful Improvements in LUTS/BPH Severity in Men Treated with Silodosin Plus Hexanic Extract of Serenoa Repens or Silodosin Alone

Abstract: To assess the rate and predictors of clinically meaningful improvements (CMI) in patients with lower urinary tract symptoms (LUTS) treated with either silodosin (SIL) alone or with a combination of SIL+ serenoa repens (Ser) hexanic lipidosterolic extract for ≥12 months. Data from 186 patients were collected. Patients completed the International Prostatic Symptoms Score (IPSS) at baseline and at follow-up assessment. Descriptive statistics and logistic regression models tested rates and predictors of CMI. Two C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
2
16
0
1
Order By: Relevance
“…The improvement of 7.2 points in mean IPSS score observed in our combination arm was also similar to the 6.4 point improvement reported for silodosin plus HESr [23] and to results reported in different RCTs which evaluated the effect of combining an alpha-blocker and a 5ARI to treat LUTS/BPH [6,[32][33][34]. The enhanced effectiveness achieved with a combination of tamsulosin and HESr over the HESr alone has also been reported in a recent meta-analysis [19].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The improvement of 7.2 points in mean IPSS score observed in our combination arm was also similar to the 6.4 point improvement reported for silodosin plus HESr [23] and to results reported in different RCTs which evaluated the effect of combining an alpha-blocker and a 5ARI to treat LUTS/BPH [6,[32][33][34]. The enhanced effectiveness achieved with a combination of tamsulosin and HESr over the HESr alone has also been reported in a recent meta-analysis [19].…”
Section: Discussionsupporting
confidence: 87%
“…This hypothesis is further supported by the results of a study which found that storage symptoms improved significantly more with TAM + HESr vs TAM alone after 12 months of treatment [22], which may be due to the HESr's anti-inflammatory action. In another study comparing the efficacy of silodosin versus silodosin plus HESr over a mean follow-up period of 13.5 months, combined therapy showed significantly more improvement from baseline on the IPSS score than silodosin alone, without any increase in adverse effects [23]. The proportion of patients showing clinically meaningful improvement (>3 IPSS points) was also higher for combination treatment (69.9% vs. 30.1% for silodosin alone; p = 0.001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, a higher than 25% improvement in IPSS was found in 68.8% and 31.2% of the patients in the combination and the monotherapy groups, respectively (p < 0.001). These data suggest that combination of a1-blocker with HESr results in greater clinically meaningful improvements in LUTS compared to monotherapy with an a-blocker [16].…”
Section: Discussionmentioning
confidence: 76%
“…A cross-sectional study compared the combination of HESr with silodosin to silodosin as monotherapy in patients treated for at least for 12 months (mean duration 13.5 months) [16]. It was reported that 69.9% of the combination therapy patients achieved the predefined clinically meaningful improvement (improvement more than three points in baseline IPSS) compared to 30.1% of patients treated only with silodosin (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%